Class, mass, and collective arbitration in national and international law - Strong, Stacie (Oxford University Press, 2013)
Class arbitration first developed in the United States in the 1980s as a means of providing large numbers of individuals with the opportunity to assert their claims at the same time and in the same proceeding. Large-scale arbitration has since spread beyond U.S. borders, with collective arbitration being seen in Europe and mass arbitration being used in the international investment regime. Class, Mass, and Collective Arbitration in National and International Law considers all three forms of arbitration as a matter of domestic and international law, providing arbitrators, advocates and scholars.